Accumulation of ammonium in Norway spruce (Picea abies) seedlings measured by in vivo 14N-NMR - Aarnes, H (Journal of experimental botany, 2007)
(14)N-NMR and (31)P-NMR have been used to monitor the in vivo pH in roots, stems, and needles from seedlings of Norway spruce, a typical ammonium-tolerant plant. The vacuolar and cytoplasmic pH measured by (31)P-NMR was found to be c. pH 4.8 and 7.0, respectively, with no significant difference between plants growing with ammonium or nitrate as the N-source. The (1)H-coupled (14) NH 4+ resonance is pH-sensitive: at alkaline pH it is a narrow singlet line and below pH 4 it is an increasing multiplet line with five signals. The pH values in ammonium-containing compartments measured by (14)N-NMR ranged from 3.7 to 3.9, notably lower than the estimated pH values of the P(i) pools. This suggests that, in seedlings of Norway spruce, ammonium is stored in vacuoles with low pH possibly to protect the seedlings against the toxic effects of ammonium ( NH 4+) or ammonia (NH3). It was also found that concentrations of malate were 3-6 times higher in stems than in roots and needles, with nitrate-grown plants containing more malate than plants grown with ammonium